Edukasi dan Literasi Anti-Korupsi Perspektif Ekonomi bagi Komunitas SSQ Holistik Internasional melalui Webinar Pengabdian kepada Masyarakat: Pengabdian - Sudarmanto, Eko; Wulandjani , Harimurti; Febrina , Ilza; Aulia , Triana Zuhrotun; Fitriani , Heny; Soepriadi , Dewi Nidia; Wardhana , M. Adhitya; Wangsih , Ingkak Chintya (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Corruption is a multidimensional problem that has significant impacts on economic performance, social welfare, and sustainable development. Efforts to prevent corruption require not only law enforcement but also the strengthening of public awareness and literacy through systematic educational approaches. This community service program aims to enhance anti-corruption understanding and literacy based on an economic perspective among members of the SSQ Holistik Internasional community through a webinar-based initiative. The program was implemented using an online participatory education approach, which included material presentations, interactive discussions, and evaluations of participants’ understanding. The educational content emphasized the relationship between corrupt practices and their impacts on economic efficiency, welfare distribution, and sustainable development. The results indicate an improvement in participants’ understanding of the fundamental concepts of corruption, the economic costs it generates, and the importance of individual and community roles in corruption prevention efforts. Overall, the webinar program proved to be an effective model of community engagement in strengthening anti-corruption literacy from an economic perspective, particularly within non-academic communities.